Does stock market investment matter for local indeterminacy? - Cunha, João B. (2012)
The purpose of this paper is to study the influence of stock market investment on the local dynamics of a standard overlapping generations (OLG) economy with capital accumulation. In particular, we focus on the emergence of local bifurcations and expectations-driven fluctuations in an economy with endogenous profits. We consider an OLG model with future consumption, decreasing returns to scale in production, and investment in both physical capital and firms’ shares. We analyze the local dynamics of our model in terms of relevant parameters, namely, the capital share of output, the elasticity of capital-labour substitution, and the degree of returns to scale. We conclude that the steady state is never a sink, and thus indeterminacy does not emerge (and hence does not hold as a possible explanation for the excess volatility puzzle at an aggregate level). The steady state is either a saddle or a source and undergoes a transcriptical bifurcation for values of the capital share of output sufficiently high. Finally, we compare steady state welfare with and without a secondary stock market. We conclude that the introduction of a secondary market for shares may correct the dynamic inefficiency that arises in a simple OLG model, improving steady state welfare when the capital share of output is sufficiently low (i.e. under strong dynamic inefficiency).